Evidence for inflammation-induced bone loss in non-radiographic axial spondyloarthritis - Akgol, Gurkan; Kamanli, Ayhan; Ozgocmen, Salih (Oxford Univ Press, 2014)
Objectives. Non-radiographic axial SpA (nr-axSpA) comprises those patients who may have clinical and laboratory features of SpA but do not have definite radiographic sacroiliitis. Bone loss (osteopenia or osteoporosis) is well recognized in AS, however, bone status in nr-axSpA is unclear. The aims of this study were to investigate BMD in patients with nr-axSpA and compare them with age-and sex-matched patients with mechanical low back pain (mLBP). The relationship between inflammation on MRI of the lumbar spine and BMD was also assessed in nr-axSpA. Methods. Patients with chronic LBP were consecutively recruited. Patients who met the Assessment of SpondyloArthritis International Society (ASAS) criteria for axial SpA but without definite radiographic sacroiliitis were defined as nr-axSpA. Spinal and femoral BMD was assessed with DXA. Lumbar spinal MRI was examined for the presence of bone oedema (BO; inflammatory lesions). Results. Forty-six patients with nr-axSpA had worse spinal but similar hip BMD, T and Z scores compared with 29 patients with LBP. 25(OH)D-3 and parathyroid hormone levels and thyroid function tests were similar between groups. Twenty nr-axSpA patients with inflammation on lumbar MRI had worse spinal and femoral BMD, T and Z scores compared with the patients without inflammation. Conclusion. Patients with nr-axSpA had significant bone loss at the lumbar spine compared with patients with mLBP. Inflammation on MRI is closely associated with low bone mass in patients who are in the very early stage of the disease.
Keywords: non-radiographic axial spondyloarthritis; bone mineral density; magnetic resonance